Black Soldier Fly (Hermetia illucens) Larvae Meal Modulates Intestinal Morphology and Microbiota in Xuefeng Black-Bone Chickens - He, Changqing; Lei, Jiaxing; Yao, Yaling; Qu, Xiangyong; Chen, Jifa; Xie, Kailai; Wang, Xingju; Yi, Qi; Xiao, Bing; Guo, Songchang; Zou, Xiaoyan (Frontiers in Microbiology, 2021)
The addition of Hermetia illucens larvae meal (HILM) to the feed could contribute to particular antimicrobial and intestinal health in animal husbandry. This study was conducted to investigate the effects of HILM on intestinal morphology and microbial diversity in different intestinal segments of Xuefeng black-bone chickens. All of 432 birds (45 weeks old) were randomly assigned to four equal groups with six replicates and 18 hens in each replicate: (A) basal diet, (B) basal diet with 1% HILM, (C) basal diet with 3% HILM, and (D) basal diet with 5% HILM. The results showed that, compared with the basal diet group, the HILM supplement significantly increased the abundance-based coverage estimator (ACE) and Chao index in cecum (p < 0.05). Diet with 1% HILM significantly increased the villus height (VH) of the duodenum (p < 0.05) and cecum microbial diversity as represented by the Simpson index (p < 0.05). In particular, 1% HILM displayed a markedly increase in the genus unclassified Bacteroidales (cecum, p < 0.05). A basal diet with 3% HILM markedly increased the beneficial genus Romboutsia (jejunum, p < 0.05). Also, principal component analysis (PCA) cluster analysis showed that 3% of HILM was more individual than other groups (p < 0.05). However, 5% HILM decreased the VH and the ratio of villus height to crypt depth (VH/CD) of the jejunum and increased beneficial bacteria such as Staphylococcus (p < 0.05), which was regarded as pathogenetic genera. In conclusion, we found that HILM improved intestinal morphology and increased microbiological diversity and species abundance. Together, dietary supplementation of 1 or 3% HILM might benefit the intestinal morphology and intestinal microbiota of Xuefeng black-bone chicken. However, the addition of 5% HILM could decrease VH and the ratio of VH/CD of the jejunum and increased pathogenetic genera. HILM was an excellent protein substitute for Xuefeng black-bone chickens, which could meet the nutritional requirements under the condition of less feed. These results provide information for HILM meal as an alternative source of soybean meal in Xuefeng black-bone chickens’ feed.